Surgical correction of 7 abdominal wall hernias using a hybrid technique (International Seven Journal of Health Research, 2024)
Incisional hernias are defects of the abdominal wall under previous scarring. They are an important epidemiological factor, as they account for 11% of laparotomy surgeries performed by surgeons. They have local and systemic symptoms, including pain, fullness, bulging, and edema, which can even lead to ischemia and tissue necrosis. Comorbidities are important aggravating factors and the surgical techniques used for correction, which consist of laparotomy and video-laparoscopy, both must be effective to avoid complications, including recurrences. The herniorrhaphy and hernioplasty techniques are constantly described in the literature, but using a mixed technique is something little seen that challenges the knowledge of the medical team and addresses the professional's judgment to encompass both prior knowledge and the patient's social and comorbid profile.